History and Dynamics of Islamic Education during the Umayyad Dynasty: Transformation, Innovation and Educational Heritage - Siti Chodijah; Nurjanah; Nurul Mawadah Salsabila; Tasya Firnandya Kamila (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islam, as a universal religion, provides life guidelines that direct humans towards happiness. Success in achieving this happiness really depends on education, because education is the key to a better life. In this context, the relationship between Islam and education becomes very close and interrelated. Islam plays an important role in forming the basic framework and foundation for the development of Islamic education, and education develops along with the growth of Islam. This shows that the history of education cannot be separated from the history of Islam. During the Umayyad Dynasty, which was the first dynasty in Islamic expansion, government faced various challenges related to conquest, territorial consolidation, and management of a multinational and multicultural empire. However, they consciously pay great attention to educational problems. In the process, the Umayyad Dynasty succeeded in developing and preserving various knowledge which is now a valuable part of the development of science. Their success in this regard also had a significant impact, especially for the European world who could access and develop this knowledge further.